IMMUNE THROMBOCYTOPENIA ONSET AND RELAPSE DURING THE COVID19 PANDEMIC. A MONOCENTER STUDY. - Giuseppe Auteri; Simona Paglia; Camilla Mazzoni; Mattia Biondo; Marta Venturi; Andre Davide Romagnoli; Daniela Bartoletti; Michele Cavo; Nicola Vianelli; Francesca Palandri (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
BACKGROUND AND OBJECTIVES